2012
DOI: 10.7448/ias.15.2.17352
|View full text |Cite
|
Sign up to set email alerts
|

Does provider‐initiated counselling and testing (PITC) strengthen early diagnosis and treatment initiation? Results from an analysis of an urban cohort of HIV‐positive patients in Lusaka, Zambia

Abstract: IntroductionBuilding on earlier works demonstrating the effectiveness and acceptability of provider-initiated counselling and testing (PITC) services in integrated outpatient departments of urban primary healthcare clinics (PHCs), this study seeks to understand the relative utility of PITC services for identifying clients with early-stage HIV-related disease compared to traditional voluntary testing and counselling (VCT) services. We additionally seek to determine whether there are any significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 37 publications
(48 reference statements)
3
36
1
Order By: Relevance
“…Existing literature has demonstrated that financial insecurity is a barrier to care and is associated with poor adherence and VF, yet no studies have assessed differences in this association between genders (25, 26, 5658). The association between financial dependency indicators and VF among women but not men in this cohort may indicate that personal financial insecurity is a risk factor for VF more specific to women in this context, as has been suggested by some findings in countries where women are often dependent upon men (16, 59, 60). …”
Section: Discussionsupporting
confidence: 65%
“…Existing literature has demonstrated that financial insecurity is a barrier to care and is associated with poor adherence and VF, yet no studies have assessed differences in this association between genders (25, 26, 5658). The association between financial dependency indicators and VF among women but not men in this cohort may indicate that personal financial insecurity is a risk factor for VF more specific to women in this context, as has been suggested by some findings in countries where women are often dependent upon men (16, 59, 60). …”
Section: Discussionsupporting
confidence: 65%
“…Coverage was reported in 19 home HTC studies 15,18,29–45 , one mobile 13 , two campaign 46,47 , three index partner/family member 4850 , five facility VCT 5155 , and five facility PITC studies 5661 . Overall, community HTC modalities achieved higher coverage than facility, with home (70%, 95% CI = 58–79) and campaign (76%, 95% CI = 49–95%) having the highest population coverage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of men out of total persons tested was reported in 25 home HTC studies 5,14,18,29,31,32,37,38,41–45,63,64,66,6872,8890 , two home with self-testing 11,75 , 10 mobile 10,13,68,72,9199 , 3 index partner 47,49,88 , 3 campaign 46,47,76 , 2 workplace 100,101 , 20 facility VCT 52,54,61,64,81,88,89,92,93,95,96,98,102107 , and 13 facility PITC 58,60,82–84,86,99,108113 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations